2020
DOI: 10.1080/14680777.2020.1713840
|View full text |Cite
|
Sign up to set email alerts
|

Now you see me, now you don’t: applying automated content analysis to track migrant women’s salience in German news

Abstract: Reading media headlines and articles about migration, one quickly gets the impression that the media discourse is focussed on migrant men. To investigate to what extend this perception actually holds true, in this study we examine the visibility of gender in media coverage about migrants. We present a validated keyword-based dictionary that allows for automatic and reliable measurement of migrants' salience (i.e., women, men) in German news coverage. A salience analysis of German migration-related news coverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…When migration intersects with gender, relevant issues arise. Studies have shown that the representation of migrant women in the news is scant (Collins, 2011;Lind and Meltzer, 2021;Silva and Mendes, 2009). According to Liu (2020), media mainly makes men the default migrant, while turning women invisible.…”
Section: Related Workmentioning
confidence: 99%
“…When migration intersects with gender, relevant issues arise. Studies have shown that the representation of migrant women in the news is scant (Collins, 2011;Lind and Meltzer, 2021;Silva and Mendes, 2009). According to Liu (2020), media mainly makes men the default migrant, while turning women invisible.…”
Section: Related Workmentioning
confidence: 99%
“…Prior research suggests that frame usage in immigration news is highly dependent on immigrant group, news outlet, and context (see, e.g., Heidenreich et al, 2019;Jacobs, Meeusen, and D'Haenens, 2018;Kroon, Trilling, Van Selm, and Vliegenthart, 2019;Lind and Meltzer, 2020;Wallace, 2018). Yet, several overarching frame-clusters reoccur.…”
Section: Immigration Discourses In Mass Mediamentioning
confidence: 99%
“…The media further the everyday bordering of migrant women by dismissing their contribution (Yuval-Davis et al 2018;Harvey 2018). Even when migrant women's economic visibility is recognized, the media discount migrant women's economic contribution and importance to the host country (Lind and Meltzer 2020). Instead, the stereotypical migrant women who make an economic impact are validated by the remittances they send home (Le Goff 2016).…”
Section: Immigrants' Economic Visibilitymentioning
confidence: 99%